Positive Solutions for Fourth-Order Singular p-Laplacian Differential Equations with Integral Boundary Conditions. (19th August 2010) - Zhang Zhang, Xingqiu Xingqiu; Cui Cui, Yujun Yujun
Abstract : By employing upper and lower solutions method together with maximal principle, we establish a necessary and sufficient condition for the existence of pseudo-C 3 [ 0, 1 ] as well as C 2 [ 0, 1 ] positive solutions for fourth-order singular p -Laplacian differential equations with integral boundary conditions. Our nonlinearity f may be singular at t = 0, t = 1, and u = 0 . The dual results for the other integral boundary condition are also given.